Aminotriazole Derivative as Anti‐Corrosion Material for Iraqi Kerosene Tanks: Electrochemical, Computational and the Surface Study. Issue 34 (10th September 2019) - Yaqo, Eva A.; Anaee, Rana A.; Abdulmajeed, Majid H.; Tomi, Ivan H. R.; Kadhim, Mustafa M.
Abstract: A triazole inhibitor, 3, 5‐di(4‐hydroxyphenyl)‐4‐amino‐1, 2, 4‐triazole (HAT), was investigated as an anticorrosion material for carbon steel in Iraqi kerosene tanks using Tafel polarization method at (303, 313, 323, and 333 K) and (100‐500 ppm) in kerosene medium. The results showed that the highest inhibition efficiency was obtained at 86.74% in 100 ppm and 333 K. The studied thermodynamic parameters show that the adsorption isotherm of the HAT inhibitor on the steel surface was identical to Langmuir isotherm. The polarization behavior revealed that this inhibitor acts as a mixed‐type inhibitor, the corrosion inhibition data have been measured and discussed in details to predict the performance of the inhibitor. The morphology of the inhibited surfaces was characterized using scanning electron microscopy/energy dispersive X‐ray spectroscopy (SEM/EDS) and an atomic force microscope (AFM). Furthermore, the Fourier transform infrared (FT‐IR) technique was used to show the interaction between HAT and the steel surface. Also, the antimicrobial activity of HAT inhibitor against some types of corrosive bacteria was examined. In addition, quantum chemical parameters were calculated by density functional theory to reveal the active centers of the inhibitor and clarify the correlation of molecular structure of the inhibitor and its efficiency of the inhibition. Abstract : This study includes a performance test of triazole derivative as a corrosion protective compound for carbon steel that used in the manufacture of oil tanks in Iraqi refineries. The polarization method was used to conduct the test. Results showed the possibility of HAT to inhibition the corrosion of steel to 86.74% at the lowest concentration. Several investigation methods were used to confirm the formation of HAT film on the steel surface.